2020
DOI: 10.1021/acsami.0c13896
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Interplay of Defects in SnO2 Quantum Dots for Blue Luminescence and Selective Trace Ammonia Detection at Room Temperature

Abstract: Defect chemistry in SnO2 is well established for resistive sensors but remains to be elusive for photoluminescence (PL) sensors. It demands a comprehensive understanding of the role of cationic and oxygen defects as well as the creation of abundant such defects to provide a selective PL signal. To accomplish it, SnO2 quantum dots (QDs ∼ 2.4 nm) are prepared without a capping agent along with other dimensions. Then, the relationship of defects with the blue-emission PL is unfolded by electron energy loss spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…The existence of oxygen vacancies is most likely to attribute for this crystalline defect. [ 24 ] The bandgap calculated from the PL data was in agreement with the bandgap obtained from Tauc's plot.…”
Section: Resultssupporting
confidence: 80%
“…The existence of oxygen vacancies is most likely to attribute for this crystalline defect. [ 24 ] The bandgap calculated from the PL data was in agreement with the bandgap obtained from Tauc's plot.…”
Section: Resultssupporting
confidence: 80%
“…Particle sizes of ∼2.4 nm for QDs and ∼25 nm of SnO 2 (800 °C) are deduced from the TEM studies, and detailed results are shown in Figure b,c, respectively. Details regarding the particle size distribution and phase conformation from TEM for both SnO 2 QDs and SnO 2 (800 °C) are provided in our previous report . The calculated band gap of SnO 2 QDs is found to be 4.2 eV against a value of 3.6 eV for SnO 2 (800 °C) from the UV–Vis study, as depicted in the Supporting Information (Figure S1).…”
Section: Resultsmentioning
confidence: 82%
“…The broad peak found in XRD patterns (Figure 2a) of and SnO 2 (800 °C) are provided in our previous report. 7 The calculated band gap of SnO 2 QDs is found to be 4.2 eV against a value of 3.6 eV for SnO 2 (800 °C) from the UV−Vis study, as depicted in the Supporting Information (Figure S1). 37 The incremental band gap for 2.4 nm particles compared with the bulk SnO 2 is attributed to the quantum confinement size effect.…”
Section: Structural and Optical Properties Of Sno 2 Npsmentioning
confidence: 88%
See 2 more Smart Citations